2003
DOI: 10.1242/jeb.00613
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and enzymatic correlates of aerobic and burst performance in different populations of Trinidadian guppiesPoecilia reticulata

Abstract: Intra-and interspecific variation in locomotor performance has long been of interest to comparative physiologists. Interspecific comparative studies of trait variation are often used to provide insights into both evolutionary adaptation and the mechanistic foundations of performance. A related approach (which reduces the problem of phylogenetic nonindependence among related species) is to use correlative analyses of natural intraspecific variation at different levels of integration (e.g. enzymes, organelles, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Kolok, 1992;Kolok and Farrell, 1994;Garenc et al, 1999;Gibb and Dickson, 2002;Odell et al, 2003;Claireaux et al, 2005). For example, intraindividual variation in V O2,max in Trinidadian guppies (Poecilia reticulata) was not significantly correlated with any of the six measured candidate traits (swimming muscle, heart and gill size and muscle CS, LDH and myofibrillar ATPase activities) after corrections for multiple comparisons (Odell et al, 2003).…”
Section: Traits Contributing To the Capacity For Whole-animal Performmentioning
confidence: 93%
See 1 more Smart Citation
“…Kolok, 1992;Kolok and Farrell, 1994;Garenc et al, 1999;Gibb and Dickson, 2002;Odell et al, 2003;Claireaux et al, 2005). For example, intraindividual variation in V O2,max in Trinidadian guppies (Poecilia reticulata) was not significantly correlated with any of the six measured candidate traits (swimming muscle, heart and gill size and muscle CS, LDH and myofibrillar ATPase activities) after corrections for multiple comparisons (Odell et al, 2003).…”
Section: Traits Contributing To the Capacity For Whole-animal Performmentioning
confidence: 93%
“…Kolok, 1992;Kolok and Farrell, 1994;Garenc et al, 1999;Gibb and Dickson, 2002;Odell et al, 2003;Claireaux et al, 2005). For example, intraindividual variation in V O2,max in Trinidadian guppies (Poecilia reticulata) was not significantly correlated with any of the six measured candidate traits (swimming muscle, heart and gill size and muscle CS, LDH and myofibrillar ATPase activities) after corrections for multiple comparisons (Odell et al, 2003). Gibb and Dickson (Gibb and Dickson, 2002) found that muscle aerobic enzyme activities (red muscle, white muscle and heart CS activity, red muscle and heart 3-hydroxy-o-acylCoA dehydrogenase activity and myoglobin content) were not significantly correlated with swimming performance in two scombrid fishes [(kawakawa tuna (Euthynnus affinis) and chub mackerel (Scomber japonicus)].…”
Section: Traits Contributing To the Capacity For Whole-animal Performmentioning
confidence: 99%
“…A number of such studies (e.g. Garland, 1984;Garland and Else, 1987;Gleeson and Harrison, 1988;Chappell and Bachman, 1995;Hammond et al, 2000;Sinervo et al, 2000;Harris and Steudel, 2002;Odell et al, 2003;Pasi and Carrier, 2003;Brandt and Allen, 2004;Kemp et al, 2005) have found an assortment of within-species associations between traits, but the combined results reveal surprisingly few consistent overall patterns (see Discussion).…”
Section: Introductionmentioning
confidence: 92%
“…Henderson et al, 2002;Howlett et al, 2009;Kirkton et al, 2009;Gębczynski and Konarzewski, 2011). However, little is known about how maximum aerobic performance and underlying traits have evolved among natural populations that experience more complex selective environments, relative to experimental evolution studies, with multiple divergent and concurrently acting sources of selection (but see Odell et al, 2003). Determining which step(s) underlie differences in M O2,max among natural populations can provide mechanistic information about the traits limiting M O2,max in a particular species, provide insight into the costs of having a high M O2,max , and establish the pace at which this ecologically relevant trait evolves in the wild.…”
Section: Introductionmentioning
confidence: 99%